2007
DOI: 10.1177/0309133307081291
|View full text |Cite
|
Sign up to set email alerts
|

New trends in digital terrain analysis: landform definition, representation, and classification

Abstract: This article provides an ontological as well as methodological evaluation of recent progress in terrain analysis. It focuses on six topographic factors, or existences, that are important in characterizing the biophysical functions of topography: elevation, surface shape, topographic position, topographic context, spatial scale, and landform object. Terrain analysis approaches are assessed according to what they really deal with, as well as how they work. Important trends are consequently identified, in which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 77 publications
0
47
0
3
Order By: Relevance
“…This is known as specific geomorphometry, whereby landforms are denoted as points, lines, polygons, or symbols. While this approach can be reliable for some dunes that have process-based arguments to support delineation (bona fide landforms following Deng, 2007), such as well-dispersed barchans on non-sandy substrates, there are no consistent process-based arguments to support the delineation of all types of aeolian dunes (referred to as vague landforms, or semantic landforms following Deng, 2007). The example of dunes at White Sands in Fig.…”
Section: Challengesmentioning
confidence: 99%
“…This is known as specific geomorphometry, whereby landforms are denoted as points, lines, polygons, or symbols. While this approach can be reliable for some dunes that have process-based arguments to support delineation (bona fide landforms following Deng, 2007), such as well-dispersed barchans on non-sandy substrates, there are no consistent process-based arguments to support the delineation of all types of aeolian dunes (referred to as vague landforms, or semantic landforms following Deng, 2007). The example of dunes at White Sands in Fig.…”
Section: Challengesmentioning
confidence: 99%
“…According to (Deng, 2007), landform classification falls into two groups: on one hand set theory where components are morphometric points (more than often pixels) yielding a segmentation of the terrain, and on the other hand category theory where landforms are identified as objects. On topographic maps, landforms are mainly qualitative objects which are not explicitly portrayed on the map but interpreted by the map reader.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have demonstrated the utility of high resolution DEMs for quantitative terrain analysis [17]- [20]. This "new generation" of topographic data has resulted in the development of new methodologies for evaluating surface landforms [21]- [25] and has helped to advance our understanding of Earth surface processes [26]- [28]. Furthermore, we have taken advantage of the increasing sophistication of quantitative algorithms for evaluating stream networks [29]- [36] that have been facilitated by the availability of increased memory and computing speed on computational platforms.…”
Section: Introductionmentioning
confidence: 99%